The Evolution of Manufacturing Technology and its Impact on Industrial Structure: An International Study - Bo Carlsson (The Research Institute of Industrial Economics (IUI), 1988)
This paper shows that plant and firm size in manufacturing, and especially in engineering industry, in several Western industrial countries has declined since the early 1970s. Two hypotheses explaining the decline are advanced. One is 'de-glomeration' or specialization: the divestiture of non-core businesses in order to free up scarce resources (particularly management time) to defend and nurture core business activities. The second hypothesis is that the emergence of new computer-based technology has improved the quality and productivity of small and medium scale production relative to standardized mass-production techniques which dominated previously.
Keywords: L25; L60; O33; 330; Manufacturing; specialisation; firm scope; technological progress; Betriebsgröße; Industrieforschung